Primary diffuse large B-cell lymphoma or lymphomatoid granulomatosis grade 3: a still-puzzling diagnosis in autopsy - Fernando Peixoto Ferraz de Campos; Aloisio Felipe-Silva; Maria Claudia Nogueira Zerbini; João Augusto dos Santos M (Autopsy and Case Reports, 2013)
Primary lung lymphoma is a rare entity accounting for approximately 0.3% of all primary neoplasia of the lung and includes diffuse large B-cell lymphoma (DLBL) and lymphomatoid granulomatosis (LYG). Considering that clinical features may be similar, whereas epidemiology, morphology, and radiological features are different, the authors report a case of a middle-aged man who presented multiple pulmonary nodules in the lower lobes and ground-glass opacities scattered bilaterally on computed tomography. Clinically, he presented a consumptive syndrome with respiratory failure and pleurisy, which progressed until death. The autopsy findings were consistent with lymphomatoid granulomatosis (LYG) grade 3/ diffuse large B-cell lymphoma (DLBL). The authors call attention to the difficulty of establishing an accurate diagnosis, mainly when the demonstration of EBV-infected atypical B-cells fails.